Fatigue behaviour and reliability of Extended Hollobolt to concrete filled hollow section - Abd Rahman, Norashidah (2012)
The need to provide mechanical connection from one side for the Hollow section connection has arisen in a number of fields and has resulted in the development of several types of so-called blind fasteners. An experimental blind bolt called the Extended Hollobolt is giving a good behaviour performance in terms of stiffness, strength and ductility. The strength performance of this system has been investigated under both monotonic and cyclic loading. However, the performance of such connections under fatigue loading is still unknown.